QUALITATIVE MODEL OF FACTORS INFLUENCING CONSTRUCTION LABOUR PRODUCTIVITY IN SOUTH AFRICA - OJ Adebowale (Journal of Construction, 2020)
Purpose Productivity in the construction industry is an important area to continually improve upon if the industry wishes to contribute meaningfully to the economy of nations. Despite the myriad of studies aimed at improving productivity in construction, poor productivity remains a major concern and threat to the survival of many construction organizations. Design A quantitative study, which entailed a sample of 523 contractors in four South African provinces and the circulation of a self-administered questionnaire, enabled the essential factors that contribute to poor productivity on South African construction projects to be determined. The data analysis entailed the computation of descriptive statistics. Findings The results indicate that inadequate workers’ skills, defective workmanship, the practice of awarding contracts to the lowest bidders, and industrial action resulting from political activities were the major threats to construction productivity. The study further revealed that most of the factors influencing construction productivity are largely dependent on one another. Value A holistic approach to addressing productivity in South African construction in the form of a qualitative model was evolved from the study.